The Potential of Jackfruit Wood as Activated Carbon for Adsorption of Heavy Metal Mercury (Hg) through Pyrolysis Method - Zimon Pereiz; Chuchita; Oksal, Efriyana; Maya Sylvani, Miranti; Irawan, Ahmad; Pebriyanto, Yunus; Hairiah, Rusliananur; Eka Jaya Prastiti, Arini; Berlisnora Dasilva, Caroline; Anatasya, Violina; Prisnanda, Risky (Al-Kimia, 2025)
Water pollution caused by heavy metal mercury is a serious problem today. This study aims to utilise jackfruit wood waste as a natural adsorbent in overcoming the problem of water pollution due to heavy metal mercury. The methods in this research include jackfruit wood preparation, hydrochar synthesis through pyrolysis, hydrochar activation, wastewater preparation, batch adsorbent optimum conditions, and dynamic adsorption process (Fixed-Bed Column). The results showed that the optimum adsorption condition was reached at 0.4 M HCl concentration, pH 3 and 80minutes contact time. The study also showed that the adsorption kinetics followed a second-order pseudo model with a rate constant of 1.712 x 10-2 g/mg.min. The research data also showed conformity with the Langmuir isotherm model, with an adsorption capacity of 63.036 mg/g. The results of this study prove that jackfruit wood waste is effectively used as raw material for making activated carbon for wastewater treatment applications in removing heavy metal mercury.